Maternal knowledge, health care seeking behaviour and associated factors for neonatal danger signs among postpartum mothers in Shashamane Town, Ethiopia: Cross sectional study - Degefa Gomora Tesfaye; Dubale Dulla Koboto; Habtamu Gezahegn (Elsevier, 2022)
Background: Knowledge of neonatal danger signs is an entry point for healthcare-seeking at health institutions. Thus, this study aimed to assess maternal knowledge, healthcare-seeking behavior, and associated factors about neonatal danger signs. Methods: A community-based cross-sectional study was conducted from June 1 to 22, 2020 among postpartum mothers in Shashamane town. Systematic random sampling was employed then data was analyzed using SPSS version 26. Variables at p < 0.05 were considered statistically significant. Results: 135 (33.2%, 95% CI: 28.8, 37.9) of the respondents had good knowledge of neonatal danger signs. Of 276 respondents who have recognized at least one neonatal danger sign on their neonate, 159 (57.6%, 95% CI; 51.74, 63.47) of them had good healthcare-seeking behavior. Marital status AOR (adjusted odds ratio) = 4.96, 95% CI: (1.99, 12.36), having less than five family members AOR = 2.09, 95% CI, (1.27, 3.44) receiving counseling during antenatal care follow-up AOR = 2.04, 95% CI, (1.17, 3.57), having postnatal care follow-up AOR = 2.37, 95% CI (1.35, 4.17), practiced feeding colostrum AOR = 3.01 (1.39, 6.50) were predictors of good knowledge of neonatal danger signs. Conclusions: Maternal knowledge of neonatal danger signs was poor. Receiving counseling during antenatal care follow-up, less than five family members and having postnatal care follow-up, marital status, feeding colostrum, and giving pre-lacteal fluid for their baby were factors significantly associated with having good knowledge of neonatal danger signs. Giving health education about neonatal danger signs and early care seeking at health institutions is recommended.